DAMPAK SOSIAL EKONOMI PEMANFAATAN LAHAN PERTANIAN SEBAGAI OBJEK WISATA DI KELURAHAN LEMPAKE KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Siti Norkhalisah; Abdullah, Zulkifli (Citra Media Publishing, 2024)
This research aims to describe the socio-economic impact of utilizing agricultural land as a tourist attraction. The method used is qualitative with a descriptive approach collected through observation, interview, and documentation techniques. The overall data obtained was analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that Betapus, which is located in Lempake urban village, Samarinda, has two attractions, namely: attractions in the form of natural scenery and attractions in the form of culinary. These two attractions are able to attract the attention of local tourists so that they have an impact on the socio-economic aspects simultaneously. The socio-economic impact of tourism activities is the increase in community livelihoods, the opening of jobs, changes in market prices, the creation of business opportunities, infrastructure development and the issue of social distance between communities arising from tourism activities.